Energy uses in Karbala governorate and its environmental affects for the year 2019 - Al-Kabby, Oday Fadhel Abd (Al-Adab Journal, 2022)
We are living in a phase where we are getting energy from coal mines oil wells and other energy, but this fuel will be consumed very quickly as it can drain all existing reserves within a period of not more than a century. Therefore, it is necessary to search for renewable natural resources, which are immature and do not cause environmental pollution.That renewable energy is the energy derived from natural resource that are replenished that are not implemented. Renewable energy is essentially different from fossil fuels from petroleum, coal, natural gas, or nuclear fuel in nuclear reactors.One of the most important features of renewable energy is that there are usually no residues of carbon dioxide (CO2) or harmful gases or increase global warming, such as when burning fossil fuels or harmful atomic waste from nuclear reactors.